Aphid Pest Management in Sweet Pepper Field with Rapeseed as a Companion Crop - Shrestha, A.; Tiwari, S.; Regmi, R.; Gautam, B. (Journal of Agriculture and Forestry University, 2022)
Sweet pepper, Capsicum annum L. is commercially grown vegetable grown for its nutritional and economical value. Sucking pests like aphids, whiteflies, thrips, mites, etc. are the major insect pest in sweet pepper fields. Farmers deliberately have been using chemical pesticides in their crop to manage various insect pest and such practices of using hazardous chemicals are harmful to human health and the biodiversity. Similarly, farmers don't have an idea of planting trap and/or companion plants and its role in natural control of pest. Hence, a study was conducted to know the population dynamics, especially to assess the aphid (Myzus persicae, Sulzer) population and its potential natural enemies by planting rapeseed as companion crop. This field experiment was conducted in six different locations of Bharatpur-23, Chitwan from Nov 2019 to Jan 2020 where three plots of sweet pepper were planted with rapeseed as companion crop and other three plots solely having no floral source around. Aphid population was recorded at weekly interval and its major natural enemies; ladybird beetle and syrphid fly. Abnormal data were squared root transformed and analyzed by using paired sample t-test. The result showed that the aphid population in sweet pepper field with companion crop was significantly lower than in sweet pepper grown without floral source (control). Highly significant number of ladybird beetles and syrphid flies were recorded in sweet pepper with companion crop compared to control. The finding is helpful to develop an integrated management protocol of sweet pepper pests with the practice of following conservation biological control strategy.